Mewujudkan Keadilan Sosial dalam Penyelesaian Sengketa Di Pengadilan Administrasi - Amarini, Indriati (Jurnal Media Hukum, 2018)
Administrative Courts in developing countries carry out more demanding tasks than those in developed countries because they have to be able to keep the balance between protecting public and individual interests. This research raises the issue of how to realize social justice in resolving a dispute in Administrative Courts. This is a doctrinal research using legal, conceptual, and comparative approaches. The research result indicates that Administrative Courts, carry out the oversight function against the acts of government officials, have to realize the justice which becomes the essence of the administrative law’s goal, that is social justice. Social justice which is built on the basis of Pancasila, functions to maintain the balance between the individual interest and the society’s rights so that the balance and harmony between the government and the people will be created. Furthermore, the Administrative Courts have to be able to realize the social justice, not only normative or procedural justices.